Interactions between Police and Persons Who Experience Homelessness and Mental Illness in Toronto, Canada: Findings from a Prospective Study. (October 2019) - Kouyoumdjian, Fiona G.; Wang, Ri; Mejia-Lancheros, Cilia; Owusu-Bempah, Akwasi; Nisenbaum, Rosane; O'Campo, Patricia; Stergiopoulos, Vicky; Hwang, Stephen W.
Objective: We aimed to describe interactions between police and persons who experience homelessness and serious mental illness and explore whether housing status is associated with police interactions. Method: We conducted a secondary analysis of 2008 to 2013 data from the Toronto, Canada, site of the At Home/Chez Soi study. Using police administrative data, we calculated the number and types of police interactions, the proportion of charges for acts of living and administration of justice, and the proportion of occurrences due to victimization, involuntary psychiatric assessment, and suicidal behavior. Using generalized estimating equations, we estimated the odds of police interaction by housing status. Results: This study included 547 adults with mental illness who were homeless at baseline. In the year prior to randomization, 55.8% of participants interacted with police, while 51.7% and 43.0% interacted with police in Study Years 1 and 2, respectively. Of 2, 228 charges against participants, 12.6% were due to acts of living and 21.2% were for administration of justice. Of 518 occurrences, 41.1% were for victimization, 45.6% were for mental health assessment, and 22.2% were for suicidal behavior. The odds of any police interaction during the past 90 days was 47% higher for those who were homeless compared to those who were stably housed (95% CI 1.26 to 1.73). Conclusions: For people who experience homelessness and mental illness in Toronto, Canada, interactions with police are common. The provision of stable housing and changes in policy and practice could decrease harms and increase health benefits associated with police interactions for this population.